Conceptual and Measurement Issues in Assessing Democratic Backsliding - Knutsen, Carl Henrik; Marquardt, Kyle L.; Seim, Brigitte; Coppedge, Michael; Edgell, Amanda B.; Medzihorsky, Juraj; Pemstein, Daniel; Teorell, Jan; Gerring, John; Lindberg, Staffan I. (PS, political science & politics, 2024)
During the past decade, analyses drawing on several democracy measures have shown a global trend of democratic retrenchment. While these democracy measures use radically different methodologies, most partially or fully rely on subjective judgments to produce estimates of the level of democracy within states. Such projects continuously grapple with balancing conceptual coverage with the potential for bias (Munck and Verkuilen 2002; Przeworski et al. 2000). Little and Meng (L&M) (2023) reintroduce this debate, arguing that “objective” measures of democracy show little evidence of recent global democratic backsliding.1 By extension, they posit that time-varying expert bias drives the appearance of democratic retrenchment in measures that incorporate expert judgments. In this article, we engage with (1) broader debates on democracy measurement and democratic backsliding, and (2) L&M’s specific data and conclusions.